2021
DOI: 10.1002/crat.202100094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and pH on Calcium Phosphate Precipitation

Abstract: Calcium orthophosphates (CaP) synthesis involves several chemical equilibria that define the phases present in the final product. From the biomaterials standpoint, it is important to gain knowledge on how synthesis parameters affect phase formation and particle size. This study evaluates the interaction between temperature (24 or 45 °C) and pH conditions (4.5, 6.5, or drifting) on CaP precipitation in terms of yield, phase formation, density, morphology, and size distribution. Calcium and phosphate solutions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In order to produce an inorganic-organic composite material with a layered structure, it is desirable that the inorganic crystal has a plate-like structure [29]. In general, the growth of calcium phosphate-based inorganic crystals is greatly influenced by the environment during crystal growth, especially the ion concentration, pH, and hydration state [30]. The water/ethanol mixture plays an important role in controlling the morphological structure of CaP particles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to produce an inorganic-organic composite material with a layered structure, it is desirable that the inorganic crystal has a plate-like structure [29]. In general, the growth of calcium phosphate-based inorganic crystals is greatly influenced by the environment during crystal growth, especially the ion concentration, pH, and hydration state [30]. The water/ethanol mixture plays an important role in controlling the morphological structure of CaP particles.…”
Section: Discussionmentioning
confidence: 99%
“…Varying the ethanol-to-water ratio (W70E30, W50E50, W30E70) may provide further control over morphology [34,35]. This will lead to a significant increase in the nucleation rate, exceeding that of other thermodynamically favorable phases such as OCP and HAp [30]. This may elucidate the fundamental factors contributing to the change in CaP morphology from one-dimensional needle-like nanowires to three-dimensional plate-like shapes [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It proved that HAP is formed at pH 6.5 and 45℃ while dicalcium phosphate dihydrate under more acidic or drifting pH [31]. Most nano-HAPs or ion substituted nano-HAP from chemical precipitation react in an alkaline media (usually adjusting to pH 10 by ammonia or sodium hydroxide solution) and higher reaction temperature to ensure the phase purity [8,[31][32][33]. Furthermore, it is worth noting that macromolecular additives (such as type Ⅰ collagen) also played a vital role in controlling the crystallization of HAP during the biomineralization process [34].On the other hand, the aging time ensured whether the reaction was complete or not.…”
Section: Reaction Conditionsmentioning
confidence: 94%
“…It suggested that pH value and temperature were predominant conditions in controlling crystal morphology and particle size of nano-HAP. Vilela conducted an experiment to verify the eff ect of temperature and pH on calcium phosphate precipitation under highly supersaturated conditions [31]. It proved that HAP is formed at pH 6.5 and 45℃ while dicalcium phosphate dihydrate under more acidic or drifting pH [31].…”
Section: Reaction Conditionsmentioning
confidence: 99%
See 1 more Smart Citation